Active metamaterial polarization modulators for the Terahertz frequency range. (July 2020) - Kindness, Stephen J.; Almond, Nikita W.; Michailow, Wladislaw; Wei, Binbin; Braeuninger-Weimer, Philipp; Hofmann, Stephan; Beere, Harvey E.; Ritchie, David A.; Degl'Innocenti, Riccardo
Abstract: Active control of chirality in the terahertz frequency range is of great importance in many scientific areas, which include research into fundamental optical phenomena, investigation of novel materials, spectroscopy, imaging, wireless communications and chemistry. The lack of efficient, integrated and fast-reconfigurable polarization modulators has hindered, so far, the full exploitation of applications in all the aforementioned fields. Metamaterials are artificial resonant elements possessing unique remarkable properties such as high efficiency and miniaturization capability. The interplay of metallic metamaterial arrays with electrostatically tunable monolayer graphene has been demonstrated to be a valid approach for the realization of a novel class of THz devices. In this work, the realization of active chiral graphene/metamaterial modulator is presented. The versatility of this experimental approach allowed the device integration with broadband sources such as terahertz time domain spectrometers as well as with quantum cascade lasers. A continuous rotation of the polarization plane > 30° has been reported with a reconfiguration speed > 5 MHz. These results pave the way to the integration of fast terahertz polarization modulators in all the applications where these devices are in great demand.